2010
DOI: 10.6107/jkha.2010.21.5.083
|View full text |Cite
|
Sign up to set email alerts
|

The Study on Housing Characteristics Preferred by Babyboomer After Retirement - Focusing on Apartment's Residents of Gangnam Region in Seoul -

Abstract: The advent of an aging society has raised the necessity for housing development to meet the growing demands of baby boomers expected to act as the main consumers in the future housing market. This study aims to identify the characteristics of apartment houses favored by baby boomers in their post-retirement plans. Based on a literature review and survey, the study is targeted at a certain baby boom generation residing in mid-sized and large-sized apartments with a floor space of more than 30 pyeong in Gangnam,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The mobility intention was more associated with the physical environment than social environment. Kim et al (2010) found that Korean baby boomers were favored an active post-retirement life where they could enjoy proper leisure without considerable change in daily-routines.…”
Section: Residential Mobility and Motivation Of Move To Cohousingmentioning
confidence: 99%
“…The mobility intention was more associated with the physical environment than social environment. Kim et al (2010) found that Korean baby boomers were favored an active post-retirement life where they could enjoy proper leisure without considerable change in daily-routines.…”
Section: Residential Mobility and Motivation Of Move To Cohousingmentioning
confidence: 99%
“…Retirement can be a time when people start thinking about making changes to where they live (Russell, 2000). More than half of Korean baby boomers have intention to move after retirement (Kim, Lee & Yoon, 2010;Im & Baek, 2011). Housing alternatives for active aging are sought for in order to strengthen a sense of community and to meet changing housing needs as well as physical, financial, and emotional needs.…”
Section: Introductionmentioning
confidence: 99%